PENGUATAN KELEMBAGAAN DAN TATA KELOLA PENGURUS DESA WISATA TERITIP - Yogiana - Mulyani; Tuatul - Mahfud; Henry - Winnarko; Abdul - Gafur; Ranti - Rustika; Ishak - Nurdin (Jurnal Abdimas Terapan, 2021)
The development of tourist villages is one of the strategic programs in national development, especially in the tourism sector. Good management of tourist villages will encourage the implementation of sustainable tourism and improve the community's economy. Although the management of the Teritip Tourism Village already has the legality from the tourism office of the Balikpapan City Youth, Sports and Tourism Office (Disporapar), they still have limitations related to governance and institutional management of the tourist village. Therefore, this village development program aims to strengthen the Teritip Tourism Village's governance and institutional management. The village development method in the Teritip sub-district includes counselling, technical skills (technical assistance / TA), and post-technical skills assistance (post-TA) in managing tourism villages. The results of this village development program produce outputs in the form of the availability of an organizational structure for the management of tourist villages and Tourism Awareness Group (Pokdarwis), along with their respective duties and functions. In addition, the results of the SWOT analysis of the tourism village management are used as a reference for the development of village development in the following year. This activity has implications for the tourism village manager assistance program model that focuses on strengthening governance and institutions.